Comparative Transcriptome Profiling Reveals Changes of microRNAs Response to Exercise in Rats with Neuropathic Pain. (3rd August 2021) - Guo, Jia-Bao; Chen, Bing-Lin; Song, Ge; Zheng, Yi-Li; Zhu, Yi; Yang, Zheng; Su, Xuan; Wang, Ying; Cao, Qing; Chen, Pei-Jie; Wang, Xue-Qiang
Abstract : There is accumulating evidence showing that exercise therapy may play an active role in peripheral neuropathic pain (NP), but its mechanism is still unclear. Studies have found that microRNAs (miRNAs) may play a role in NP by regulating pain-related target genes. Therefore, we aimed to explore the changes of miRNA and mRNA of dorsal root ganglion (DRG) after NP in response to exercise with transcriptome technology. The chronic constriction injury (CCI) model was established, and rats were randomly allocated into three groups, namely, the sham-operated, CCI, and CCI-exercised groups. L4-L6 DRG tissue was taken for RNA-sequencing, and the differentially expressed genes (DEGs) were determined through bioinformatics analysis. Real-time PCR was used to confirm the accuracy. A total of 4 overlapping differentially expressed miRNAs and 186 overlapping differentially expressed mRNAs were identified in the two comparisons of the sham-operated group versus the CCI group and the CCI group versus the CCI-exercised group. Among these DEGs, miR-145-5p, miR-341, miR-300-5p, miR-653-5p, Atf3, Cacna2d1, Gal, and Ctss related to NP were validated by real-time PCR. DEGs between the CCI and CCI-exercised groups were enriched in HIF-1 signaling pathway, Rap1 signaling pathway, and neurotrophin signaling pathway. This study provides an understanding of the adaptive mechanisms after exercise of NP, and these DEGs in DRG might play a role in NP by stimulating the enriched pathways.